Adaptive algorithms robust to impulsive noise with low computational cost using Order Statistic - Soria, Emilio; Martín, José D.; Serrano, Antonio J.; Magdalena, Rafael; Martínez, Marcelino; Gómez-Sanchis, Juan (IFAC Proceedings Volumes, 2009)
In this paper a family of adaptive algorithms robust to impulsive noise and with low computational cost are presented. Unlike other approaches, no cost functions or filtering of the gradient are considered in order to update the filter coefficients. Its initial basis is the basic LMS algorithm and its sign-error variant. The proposed algorithms can be considered as some sign-error variants of the LMS algorithm. The algorithms are successfully tested in terms of accuracy and convergence in a standard system identification simulation in which an impulsive noise is present. Simulations show that they improve the performance of LMS variants that are robust to impulsive noise.